Motivational strategies to develop the listening skills in the teaching-learning process of English language applied in the students of eighth and ninth years of basic education in the colegio nacional mixto Dr. José María Velasco Ibarra, in El Guabo, academic period 2014-2015. - Romero Orbes, Jenny Marjorie (My University, 2015)
El rol del maestro en la enseñanza del idioma inglés es muy importante para alcanzar los objetivos de la educación. Los maestros que usan estrategias motivadoras enseñan a los jóvenes a utilizar las herramientas que incrementan el conocimiento y les ayudan a adquirir la habilidad de entender las muchas facetas de su medio ambiente, con el fin de fomentar la curiosidad intelectual, animar el pensamiento crítico y desarrollar sus habilidades personales para ser capaces de comunicarse con otros usando el segundo idioma. Por esta razón, esta investigación busca determinar el nivel de importancia de las estrategias motivacionales en el proceso de enseñanza aprendizaje del idioma inglés para desarrollar la habilidad de escuchar en los estudiantes de 8vo y 9no grado de Educación General Básica en el Colegio Dr. José María Velasco Ibarra de la ciudad de El Guabo, provincia de El Oro, durante el período académico 2014-2015.
The role of the teacher in the teaching of English is very important to achieve the goals of education. Teachers who use motivational strategies to teach young people to use the tools that increase knowledge and help them acquire the ability to understand the many facets of their environment , in order to foster intellectual curiosity , encourage critical thinking and develop personal skills to be able to communicate with each other using the second language. Therefore , this research aims to determine the level of importance of motivational strategies in the process of learning the English language to develop listening skills in students of 8th and 9th grade of basic general education at the College Dr. José María Velasco Ibarra city of El Guabo , El Oro province , during the academic period 2014-2015 .*
Keywords: MOTIVATIONAL; DEVELOP; SKILL; THEACHING-LEARNING